2016
DOI: 10.17796/1053-4628-40.1.21
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health Characteristics of Preschool Children with Autistic Syndrome Disorder

Abstract: autistic children have a relative age of one half, meaning they function at half the level of normally developed children at their chronological age, more eating problems and more persistent oral habits yet no correlation to dental health could be shown. Caries experience of autistic children was lower than in the control group, maintaining good oral hygiene is difficult for autistic children yet their gingival health was found to be good.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
52
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 12 publications
2
52
0
4
Order By: Relevance
“…The initial search from online electronic databases yielded 2393 records, and 1629 remained after removal of duplications. The screening of titles and abstracts resulted in 76 potentially eligible studies, among which 39 eligible studies (reported from 41 articles) were identified and formed the basis of qualitative analysis (24 studies assessed dental plaque, 21 studies assessed gingival or periodontal status, and 32 studies assessed caries status). Twenty‐six studies were suitable for meta‐analysis (12 studies on dental plaque, 8 on periodontal status, and 23 on caries).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The initial search from online electronic databases yielded 2393 records, and 1629 remained after removal of duplications. The screening of titles and abstracts resulted in 76 potentially eligible studies, among which 39 eligible studies (reported from 41 articles) were identified and formed the basis of qualitative analysis (24 studies assessed dental plaque, 21 studies assessed gingival or periodontal status, and 32 studies assessed caries status). Twenty‐six studies were suitable for meta‐analysis (12 studies on dental plaque, 8 on periodontal status, and 23 on caries).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty‐four studies assessed the severity of dental plaque accumulation using the following indices: the Simplified Oral Hygiene Index (16 studies), Plaque Index of Silness and Löe (five studies), Patient Hygiene Performance Index of Podshadley and Haley (one study), Visible Plaque Index of Ainamo and Bay (one study), oral hygiene partial scoring modification described by Ramfjord (one study), and an unspecific oral hygiene index (one study) (Table SIII, online supporting information).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations